BROWNFIELDS - NOVÝ OBYTNÝ SOUBOR V HISTORICKÉM CENTRU BUČOVIC - Doláková, Pavlína (Vysoké učení technické v Brně. Fakulta architektury)
Cílem urbanisticko-architektonické studie je návrh obytného souboru, který bude koncipován pro bydlení v rodinných a bytových domech. Jakožto území na rozhraní mezi železniční tratí a historickou zástavbou, kterou tvoří bučovický zámek, je práce zaměřena na začlenění bytové zástavby do tohoto místa a využití jedinečnosti okolí.

The aim of the urban-architectural study is to design a residential complex that will be designed for living in family and residential buildings. As a territory between the railway track and the historic building, which is the Bučovice chateau, the work is focused on the integration of housing development into this place and the use of the uniqueness of the surroundings.
BROWNFIELDS - A NEW RESIDENTIAL AREA IN THE HISTORICAL CENTER OF BUČOVICE CITY
Keywords: Bučovice; zámek; obytný soubor; urbanistická studie; brownfield; bydlení v historickém prostředí; bytový dům; urbanisticko-architektonická studie; rodinné domy; řadové domy; Bučovice; chateau; residential complex; urban study; brownfield; housing in historical environment; apartment building; urban-architectural study; family houses